2014
DOI: 10.1111/ajt.12913
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Safety and Rationale for Cinacalcet Posttransplant Hyperparathyroidism and Hypercalcemia

Abstract: Patients with stage 5 chronic kidney disease usually develop secondary hyperparathyroidism with concomitant parathyroid gland hyperplasia. Following renal transplantation, parathyroid glands usually undergo slow involution, resulting in lower parathyroid hormone (PTH) levels and abatement of hypercalcemia and hypophosphatemia. A subset of patients has more severe hyperparathyroidism posttransplant, and develops persistent and significant hypercalcemia.In this issue of the American Journal of Transplantation, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…However, it is important to reiterate that cinacalcet is not yet approved for use in renal transplant recipients. Moreover it is not clear whether either of these treatments is appropriate even if safety and biochemical efficacy are assumed [11]. Bone disease following kidney transplantation is a complex problem with multiple etiologies related to dialysis, corticosteroid therapy, calcineurin inhibitors, and persistent hyperparathyroidism [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to reiterate that cinacalcet is not yet approved for use in renal transplant recipients. Moreover it is not clear whether either of these treatments is appropriate even if safety and biochemical efficacy are assumed [11]. Bone disease following kidney transplantation is a complex problem with multiple etiologies related to dialysis, corticosteroid therapy, calcineurin inhibitors, and persistent hyperparathyroidism [13].…”
Section: Discussionmentioning
confidence: 99%
“…There were no new safety signals although follow-up was rather short. These findings are very encouraging but further studies are needed particularly in regard to long-term clinical outcomes [11]. Moreover, there is an unresolved issue as to whether cinacalcet should be discontinued or pursued at the time of kidney transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…20 Alternatively, given the high prevalence of low bone turnover in transplant recipients with hypercalcemia and hyperparathyroidism, it has been suggested that cinacalcet or even parathyroidectomy may exacerbate adynamic bone disease. 22 Adynamic bone disease can be indirectly assessed by bone turnover biomarkers. 23 Among them, alkaline phosphatase is the best.…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of data regarding the optimal management of tertiary hyperparathyroidism. 22 A cost-utility analysis has been reported comparing subtotal parathyroidectomy with cinacalcet in patients on dialysis with severe hyperparathyroidism. 33 This study concluded that surgery was more cost effective if cinacalcet treatment duration reached 16 months.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we prefer to measure the PTH in transplant candidates 2–4 weeks after stopping the calcimimetic as part of the evaluation for transplant. If the PTH is < 800 pg/mL, the patient’s risk of hypercalcemia post-transplant appears to be low [ 16 ]. If the PTH is > 1000 pg/mL, this is indicative of severe HPT-related bone disease.…”
Section: Pre-transplant Management Of Secondary Hyperparathyroidismmentioning
confidence: 99%